Fusion of the Median and Musculocutaneous Nerves Masquerading as Biceps' Innervation from the Median Nerve - Antonopoulos, Ioannis; Ampadiotaki, Margarita- Michaela; Tsikouris, George; Chiotis, Ioannis; Tsakotos, Georgios; Pathiakis, Ioannis; Troupis, Theodore G. (Journal of Brachial Plexus and Peripheral Nerve Injury, 2023)
Embryologically, the musculocutaneous nerve (MCN) comes from the lateral root of the median nerve, and thus numerous anatomical variations concerning the formation and branching pattern of these two nerves of the brachial plexus have been described. In this case study, we describe a relatively uncommon case of fusion of the median and MCNs that was identified during routine teaching dissection of a male human cadaver. The identification of this anatomical variation requires awareness of the embryological background, as it may be confused with biceps innervation from the median nerve or the existence of a communicating branch between the two nerves. In addition, awareness of such anatomical variations is of undisputable significance for the safety of surgical operations in the brachial plexus and the arm in general.
Keywords: median nerve; musculocutaneous nerve; biceps' innervation; brachial plexus